Inventory of Amphibian Species (Order Anura) in Ujung Kulon National Park - Siti Rosidah; Indria Wahyuni; Usman; Mahrawi; Dwi Ratnasari; Ika Rifqiawati (Berkala Ilmiah Biologi, 2022)
Abstract: This research was conducted to provide an amphibian (order Anura) species list in the Ujung Kulon National Park, Banten, Indonesia. The study was conducted in June-July 2021. The location of the study was determined using a purposive sampling method, namely based on the type of amphibian habitat located in four areas of Ujung Kulon National Park, namely Handeulum Island, Cigenter, Peucang Island, and Cidaon. Sampling was carried out in the morning at 07:00-11:00 WIB and in the evening at 19:00-22:00 WIB using the VES (Visual Encounter Survey) method combined with line transects. The observation station has an average temperature of 25-30˚C, soil moisture 62-69%, air humidity 80-89%, light intensity 832-1443 lux, and soil pH 6.5-6.7. The amphibians obtained were 10 species from 5 families. The Family Dicroglossidae is the most found. The most common species found were at station 3 on Peucang Island and station 4 Cidaon. Differences in the composition of amphibians are caused by different habitats at each station and environmental factors.